2019
DOI: 10.1038/s41598-019-49343-2
|View full text |Cite
|
Sign up to set email alerts
|

Dynamic Remodeling of the Host Cell Membrane by Virulent Mycobacterial Sulfoglycolipid-1

Abstract: Lipids dictate membrane properties to modulate lateral membrane organization, lipid/protein diffusion and lipid-protein interactions, thereby underpinning proper functioning of cells. Mycobacterium tuberculosis harnesses the power of its atypical cell wall lipids to impact immune surveillance machinery centered at the host cell membrane. However, the role of specific virulent lipids in altering host cellular functions by modulating membrane organization and the associated signaling respo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
40
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
8
1

Relationship

2
7

Authors

Journals

citations
Cited by 32 publications
(47 citation statements)
references
References 49 publications
3
40
0
Order By: Relevance
“…Aside from interactions with specific surface receptors on human macrophages, it remains unknown whether SLs can influence the dynamics of host cell membranes since SLs are located at the host-bacterium interface. It was recently found that SL-I mediates the remodeling of THP-1 cell membranes in a time and concentration-dependent manner that resulted in increased host membrane fluidity and altered membrane-associated signaling [47]. This evidence supports the finding that SLs inhibit the formation of TLR2/TLR1 and TLR2/TLR6 heterodimers in the host cell membrane [46].…”
Section: Sulfolipids (Sls)supporting
confidence: 71%
“…Aside from interactions with specific surface receptors on human macrophages, it remains unknown whether SLs can influence the dynamics of host cell membranes since SLs are located at the host-bacterium interface. It was recently found that SL-I mediates the remodeling of THP-1 cell membranes in a time and concentration-dependent manner that resulted in increased host membrane fluidity and altered membrane-associated signaling [47]. This evidence supports the finding that SLs inhibit the formation of TLR2/TLR1 and TLR2/TLR6 heterodimers in the host cell membrane [46].…”
Section: Sulfolipids (Sls)supporting
confidence: 71%
“…Changes in membrane lipid composition and organization are generally thought to influence many cellular functions. Our findings go beyond the functional observations that Mtb uses envelope lipids to remodel the host membrane and divert macrophages functions (Laneelle and Tocanne, 1980;Sut et al, 1990;Welin et al, 2008;Augenstreich et al, 2019;Mishra et al, 2019). They provide evidence that insertion of lipids into host cell membranes helps the bacteria exploit membrane partners that direct the cell's responses.…”
Section: Discussionmentioning
confidence: 49%
“…Whether DIMs promote the targeting of Mtb through autophagy machinery also remains to be investigated [26]. Another work has reported that purified Mtb SLs promote GFP-LC3 puncta accumulation in macrophages [27]. Again, it is unclear whether SLs activate autophagy or prevent LC3 turnover.…”
Section: Introductionmentioning
confidence: 99%